UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KENIKIR (Cosmos caudatus Kunth) DENGAN METODE FERRIC REDUCING ANTIOXIDANT POWER - Abidin, Zainal; Salsabila Ihsan, Nur Rifdah; Aminah, Aminah (Makassar Pharmaceutical Science Journal (MPSJ), 2025)
Antioxidants are defined as inhibitors that work with the oxidation process, even at relatively small concentrations. Antioxidants are substances that can delay, slow down and prevent the oxidation process. Kenikir leaves contain flavonoid compounds, polyphenols, saponins, tannins, alkaloids and essential oils and also contain bioactive compounds such as ascorbic acid, quercetin, chlorogenic acid and polyphenolic compounds which function as antioxidants. The aim of this research was to determine the antioxidant activity test of the ethanol extract of Kenikir leaves using the FRAP (Ferric Reducing Antioxidant Power) method. The Kenikir leaf extraction method uses the maceration method with 96% ethanol solvent to obtain Kenikir leaf ethanol extract. The ethanol extract of Kenikir leaves was reacted with several FRAP reagents and then measured using a UV-Vis spectrophotometer at a maximum wavelength of 720 nm. Quercetin as a comparison with the quercetin test results obtained a linearity equation of y = 0.0117x + 0.4212 with a correlation coefficient value of r = 0.9986. The results showed that the ethanol extract of Kenikir leaves had an antioxidant activity of 12.7464 mgQE/g extract.